Meat demand model in Iran: a restricted source-differentiated almost ideal demand system approach - Elham Pourmokhtar; Reza Moghaddasi; Amir Mohammad Nejad; Seyed Safdar Hosseini (Universitas Islam Indonesia, 2018)
The gradual disappearance of pastures due to overgrazing of cattle, high cost of meat (red and poultry) and gradual increasing domestic demand, so far, meat imports in Iran have been inevitable to meet domestic needs. In this article, the authors have used RSDAIDS model, the economic factors (meat prices and costs) and non-economic factors (prevalence of diseases) affecting the demand for meat (beef and poultry) during the years 2002-16 have been investigated. The results of this study shed light on Iran consumer preferences with regard to imported meat. This is the first study that analyzes the Iran meat demand differentiated by source.In this study, it was observed that Brazil, United Arab Emirates, Ireland and Turkey were the most gainer from an increase in the size of the imported meat market ofIran. Also, these countries had a competitive advantage compared with other export sources.